2005
DOI: 10.1007/s00221-005-2354-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromagnetic motor fields accompanying self-paced rhythmic finger movement at different rates

Abstract: We have studied the effect of movement rate on MEG activity associated with self-paced finger movement in four subjects to determine whether the amplitude or latency of motor-evoked activity changes across a range of rates. Subjects performed a continuation paradigm at 21 distinct rates (range: 0.5-2.5 Hz) chosen because of their relevance for many types of sensorimotor coordination (e.g. musical performance). Results revealed a pair of field patterns whose topography and temporal dynamics were similar across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
5
0
3
Order By: Relevance
“…The lack of difference in amplitude and dipole intensity between twins and unrelated pairs was likely not a result of the varied movement intensity of individual subjects, but rather that amplitude and dipole intensity of MEF1 are affected by different environmental factors. In previous studies, it has been reported that amplitude and dipole moment of MEF1 does not change even if finger movement intensity and frequency are changed (Mayville et al, 2005; Onishi et al, 2006). In addition, Van’t Ent et al (2010) reported that amplitude of somatosensory-evoked magnetic field (SEF) is influenced by genetics.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of difference in amplitude and dipole intensity between twins and unrelated pairs was likely not a result of the varied movement intensity of individual subjects, but rather that amplitude and dipole intensity of MEF1 are affected by different environmental factors. In previous studies, it has been reported that amplitude and dipole moment of MEF1 does not change even if finger movement intensity and frequency are changed (Mayville et al, 2005; Onishi et al, 2006). In addition, Van’t Ent et al (2010) reported that amplitude of somatosensory-evoked magnetic field (SEF) is influenced by genetics.…”
Section: Discussionmentioning
confidence: 93%
“…It is difficult, if not impossible, to gain insight into this aspect solely from behavioral data (Wing 2002). From imaging studies we know that multiple brain areas are involved in motor timing tasks in a task-dependent fashion (Turner et al 2003;Mayville et al 2005). In view of the discussed differences between constant frequency tapping and tapping with intentional drift, it is therefore rather likely that different networks were involved in both forms of tapping, potentially controlling repetitive movements with different temporal properties.…”
Section: Discussionmentioning
confidence: 99%
“…Deux études complémentaires ont exploré les effets de la fréquence des stimuli sur l'activité électromagnétique des aires corticales auditives (Carver et al, 2002), et l'incidence de la vitesse des mouvements sur l'activité électromagnétique des aires motrices (Mayville et al, 2005). La première de ces deux études visait à compléter les résultats obtenus sur l'intégration sensorimotrice a utilisé une mesure en MEG par 141 voies de l'activité produite par une stimulation auditive dont la fréquence est variée de 0.6 à 8.1 Hz.…”
Section: La Direction Du Courant Et Celle Du Champ Magnétique Peuveunclassified
“…La connexion entre ces deux types de transitions nécessitera de plus amples développements mais apparaît comme une piste à suivre des plus intéressantes. L'étude de l'évolution de l'activité électromagnétique quand la vitesse de mouvements de flexion de l'index est augmentée a été implémentée au moyen d'un paradigme de continuation (Jantzen et al, 2004b(Jantzen et al, , 2005Mayville et al, 2005 ;Wing & Kristofferson, 1973). Afin de contrôler la vitesse du mouvement les sujets devaient se synchroniser avec un métronome puis continuer leurs mouvements à la fréquence prescrite après arrêt de ce même métronome.…”
Section: La Direction Du Courant Et Celle Du Champ Magnétique Peuveunclassified